(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Initial evaluation of the rehabilitation effectiveness for dysphagia patients after stroke using the Mann Assessment Swallowing Ability (MASA). Subject and methods: 30 stroke patients at Rehabilitation Center, Bach Mai Hospital. The study was conducted using a before-after comparative design. A convenience sampling method was used to recruit participants. Results: The proportion of patients requiring feeding via gastrostomy decreased from 93.3% at the time of the initial evaluation to 23.7% at discharge (p < 0.001). The mean of MASA before and after rehabilitation increased from 151.3 ± 20.24 to 165.7 ± 19.77 (p < 0.001), along with significant changes in the severity of dysphagia and aspiration according to the MASA classification. The most commonly used swallowing rehabilitation techniques were thermal-tactile stimulation, food texture modification, the Shaker exercise, and oral motor exercises. Regresstion analysis found a negative correlation between the pharyngeal phase score and thermal-tactile stimulation (OR = 0.55; 95% CI = 0.32-0.92). In the patient group with a MASA comprehension score ≥ 6, there was an inverse relationship between tongue coordination score and oral motor exercises (OR = 0.45; 95% CI = 0.20-0.99). Conclusion: Rehabilitation is important to improve swallowing function in stroke patients. The MASA is useful in the clinical assessment for patients with swallowing disorders.